Pengembangan Sistem Informasi Manajemen Untuk Meningkatkan Keunggulan Kompetitif Organisasi: Strategi dan Implementasi dalam Era Digital - Sumaiya Nurhasanah Lubis; Muhammad Irwan Padli Nasution (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The development of Management Information Systems (MIS) has become a strategic driver in strengthening organizational competitiveness in the digital age. Through a literature review, this article analyzes digital strategies, integrated technologies such as cloud computing, big data, and artificial intelligence (AI), as well as the main challenges faced during MIS implementation. The studies reviewed 2020–2025 highlight that MIS improves operational efficiency, supports strategic decision-making, and strengthens interdepartmental collaboration. The application of analytical tools and open system architecture also enables organizations to respond more quickly to market changes, strengthening long-term competitiveness. Human resource readiness, data governance, and effective change management emerge as key factors for successful implementation. The study concludes that aligning MIS development with organizational goals and digital transformation initiatives acts as a crucial catalyst for competitive advantage, while providing practical recommendations for a sustainable implementation roadmap.